Insulin resistance and its relation to inflammatory status and serum lipids among young women with PCOS - S, Asmathulla; Vani K, Rupa; S, Kripa; R, Rajarajeswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The incidence of polycystic ovarian syndrome (PCOS) is increasing among young women. PCOS women have decreased insulin sensitivity independent of body mass index with increase in lipid levels. Studies on measuring inflammatory status in PCOS showed varying results. The inter-relationship between inflammatory status, insulin resistance and lipid levels among PCOS women was studied. Methods: Twenty PCOS women and 20 healthy controls of age 18-25 years were recruited. Fasting blood samples were collected for estimation of serum glucose, insulin levels, lipid levels and C-reactive protein (CRP) concentration. Insulin resistance was determined by homeostasis model assessment (HOMA-IR) index. Results: PCOS women had significant increase in fasting insulin, HOMA-IR and triglycerides compared to healthy controls. HOMA-IR was positively associated with serum triglycerides, VLDL levels and CRP levels among PCOS subjects. Total Cholesterol was positively associated with CRP. Regression analysis showed HOMA-IR as a sole parameter strongly linked with PCOS women. This indicates that, IR is an independent pathogenic variable linked with PCOS which in turn showed positive association with CRP and triglycerides. Conclusion: IR is the hallmark of PCOS among young adolescent women. IR is associated with elevated CRP and triglyceride levels. Taking measures to increase insulin sensitivity, may help in altering dyslipidemia and inflammatory status, thereby reducing CVD risk among young women with PCOS.